2012
DOI: 10.1111/j.1365-2958.2012.08100.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia co‐opts the rod shape‐determining proteins MreB and Pbp2 for cell division

Abstract: SummaryChlamydiae are obligate intracellular bacterial pathogens that have extensively reduced their genome in adapting to the intracellular environment. The chlamydial genome contains only three annotated cell division genes and lacks ftsZ. How this obligate intracellular pathogen divides is uncharacterized. Chlamydiae contain two high-molecular-weight (HMW) penicillin binding proteins (Pbp) implicated in peptidoglycan synthesis, Pbp2 and Pbp3/FtsI. We show here, using HMW Pbp-specific penicillin derivatives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
159
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 99 publications
(178 citation statements)
references
References 51 publications
17
159
0
Order By: Relevance
“…However, recent studies using electron cryotomography, mass spectrometry as well as in situ fluorescent labeling demonstrated that some species synthesize a unique type of PG which localizes to the division site (Pilhofer et al, 2013; Liechti et al, 2014). Further, it was shown that PBP2 and PBP3 (FtsI), which are involved in PG synthesis in other bacteria, are required for cell division in an MreB (bacterial actin homolog)-dependent manner in Chlamydia trachmotis (Ouellette et al, 2012). In the Chlamydiae Waddlia chondrophila , RodZ (a regulator of MreB) and MreB localize at the division site, and biosynthesis of PG precursor lipid II is required for the recruitment of RodZ to the division site (Jacquier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies using electron cryotomography, mass spectrometry as well as in situ fluorescent labeling demonstrated that some species synthesize a unique type of PG which localizes to the division site (Pilhofer et al, 2013; Liechti et al, 2014). Further, it was shown that PBP2 and PBP3 (FtsI), which are involved in PG synthesis in other bacteria, are required for cell division in an MreB (bacterial actin homolog)-dependent manner in Chlamydia trachmotis (Ouellette et al, 2012). In the Chlamydiae Waddlia chondrophila , RodZ (a regulator of MreB) and MreB localize at the division site, and biosynthesis of PG precursor lipid II is required for the recruitment of RodZ to the division site (Jacquier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One class of genes for which the bacterium has few annotated examples is cell division, and Chlamydia lacks FtsZ, a central coordinator of the division apparatus. We have previously implicated MreB as a potential substitute for FtsZ in Chlamydia (Ouellette et al, 2012). Thus, to identify new chlamydial cell division components, we searched for proteins that interacted with MreB.…”
mentioning
confidence: 98%
“…Interestingly, euo contains three Trp residues in C. pneumoniae (versus two in C. trachomatis), and its transcript levels are highly elevated during IFN-␥-mediated persistence. To begin testing our hypothesis that chlamydial transcription during IFN-␥-mediated Trp limitation is dependent on the Trp codon content of the gene being transcribed, we measured the transcript levels of eight genes, with various Trp codon contents, representing diverse functions from cell division (mreB and rodZ) (50,51), to transcription (nusA, nusG, dksA, and rho), to translation (obg) (52), to metabolism (ubiA). MreB, DksA, NusA, and Rho contain no Trp.…”
Section: Chlamydial Transcriptional Responses Are Highly Reproduciblementioning
confidence: 99%